2022
DOI: 10.2427/12954
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to pay for vaccination against hepatitis b and its determinants: the case study of an industrial district of Pakistan

Abstract: Willingness to pay (WTP) for vaccination of hepatitis disease is a good measure to monetize the physical effects of a disease into monetary values. Therefore, the present study aims to find the willingness to pay for self-paid vaccines for hepatitis and its determinants in an industrial district Faisalabad, Pakistan. Primary data was collected from 200 nonpatients of hepatitis which were personally interviewed by using convenient sampling method. A scenario was presented to the selected respondent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 15 publications
3
4
0
Order By: Relevance
“…In this study as the knowledge and attitude scores of the respondents increased by one their willingness to pay for the HBV vaccine will be increased by 6.76 and 27.11, respectively. The findings are consistent with other studies (29,(42)(43)(44).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In this study as the knowledge and attitude scores of the respondents increased by one their willingness to pay for the HBV vaccine will be increased by 6.76 and 27.11, respectively. The findings are consistent with other studies (29,(42)(43)(44).…”
Section: Discussionsupporting
confidence: 94%
“…An interviewer-administered questionnaire was used to collect the data. The tool was developed after the literature review of the related studies ( 12 , 14 , 29 ). It was first prepared in English, then translated to Amharic (the local language), and was translated back to English to check for its consistency with a language expert.…”
Section: Methodsmentioning
confidence: 99%
“…The association between age and willingness to pay for routine immunization services has been mixed in the existing literature [40,[44][45]. In this study, respondent's age was found to have a negative effect on WTP, this was similar to findings by Ossai et al 2016 that younger age group were more likely to pay for routine immunization services in Enugu [44].…”
Section: Discussionsupporting
confidence: 83%
“…In this study, respondent's age was found to have a negative effect on WTP, this was similar to findings by Ossai et al 2016 that younger age group were more likely to pay for routine immunization services in Enugu [44]. Meanwhile, Sarker et al 2020 had a contrary findings on WTP for oral cholera vaccine and age of the study participants in urban areas of Bangladesh; this finding might be as a result that the authors used only a single antigen i.e cholera vaccine, rather than using the whole antigen under the guidelines of National Programme on Immunization in Bangladesh [45]. Also, findings by Rezaei et al among mothers in Iran indicate negative relationship between age of the study participants (mothers) and WTP for routine immunization services [37] Meanwhile, distance to the nearest health facility has been found to have a negative effect on WTP in this study i.e short distance increased the likelihood of WTP; although the relationship was not found to be statistically significant.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation